Faktor-Faktor Yang Berpengaruh Terhadap Kejadia Abortus Inkomplit Di Rsud Gambiran Kota Kediri Tahun 2016 - Mooren Lia Luthfiana; Triatmi Andri Yanuarini; Mika Mediawati (coba, 2017)
Risk factors originating from the mother are maternal genetic abnormalities, age, parity, history of abortion, pregnancy interval, hormonal, maternal illness (anemia, infection, hypertension, kidney disease, liver disease, diabetes mellitus disease) and external influences such as medicine treatment, cigarettes, and others. The purpose of this study is to determine the factors that have an impact on the incidence of miscarriage in Gambiran Regional Public Hospital Kediri. This research used case control design. The population in this study were 198 maternal record data of women who had miscarriage and pregnant mothers until they gave birth. Sampling was done through simple random sampling and data collection using recapitulation of research data sheet instrument that was analyzed with Chi Square. The statistics test using Chi Square obtained χ value2 of 22.673 so that H0 was rejected which means there is age effect on the incidence of miscarriage. On the parity variable the value was 21.134 so that H0 was rejected which means there is parity influence on miscarriage. At the pregnancy interval variable the value was 21.569 so that H0 was rejected which means there is influence of pregnancy interval to miscarriage. In the abortion history variable the value was 1.992 so that H0 was accepted which means there is no effect of abortion history on miscarriage. Health workers are expected to share knowledge of the causes, prevention efforts and improve the quality of services in reducing miscarriage incidence.